T-Cell/ Histiocyte-Rich Large B-Cell Lymphoma of Posterior Mediastinum: A Case of Diagnostic Dilemma - Mohapatra, Manisha; Sarma, Yerraguntala Subramanya (Annals of Pathology and Laboratory Medicine, 2019)
T-cell/histiocyte-rich large B-cell lymphoma (THRLBCL) is a rare aggressive type of diffuse large B-cell lymphoma (DLBCL) characterized by presence of less than 10% of large atypical B lymphocytes i.e. malignant lymphocytes in the background of T lymphocytes. Pathophysiology is thought to involve cytotokine mediated evasion of T cell immune response by malignant B cells. Mostly, affects lymph node, but can occur in extra nodal sites like bone marrow, liver and spleen. THRLBCL arising in mediastinum is extremely rare. Till date, there are only two case reports ascribing the occurrence of THRLBCL in mediastinum. Herein, we report another case of 49 years old female causing diagnostic dilemma initially but later on could be diagnosed accurately as THRLBCL of posterior mediastinum based on radiological and histopathological examination findings, immunhistochemistry (IHC) result and treated successfully.